Security measures - (:unkn) unknown (My University, 2010)
Güvenlik tedbirleri, tehlikeli suçlulara karşı toplumu korumak amacıyla uygulanan ceza hukuku yaptırımlarıdır. Güvenlik tedbirleri, şu dört şartın gerçekleşmesi halinde uygulanabilir. İlki, bir suçun işlenmiş olmasıdır. İkincisi, tehlikeli bir halin var olmasıdır. Üçüncü şart, güvenlik tedbirlerinin kanunda öngörülmüş olmasıdır. Nihayet son şart, güvenlik tedbirlerinin yargı kararına binaen uygulanabilmesidir.

Security measures are the criminal sanctions that are applied in order to protect the society. Security measures shall be applied if four applicability conditions are met. The fi rst is that a crime must have been committed. The second is that a preceriousness must have been in existence. Lastly, the third and fourth conditions are that security measures must have been prescribed by law and based on a judicial decision.
güvenlik tedbirleri
Keywords: Hukuk